Pengaruh Model Pembelajaran Bola Voli Suhadi Terhadap Kemampuan Kognitif Anak Sekolah Dasar - - Suhadi (Jurnal Pendidikan Jasmani Indonesia, 2005)
This research aim is to describe correlation on Suhadi volley ball learningmodel to cognitive ability of elementary school children in SD Negeri Sabdodadi,Bantul, Yogyakarta.This research is using pre experimental method with the one group pre test-post testdesign. The research subject is 26 children in grade 5 SD Negeri Sabdodadi, Bantul,Yogyakarta. Subject received volley ball learning assistance with 4 model of volleyball learning designed by Suhadi in 8 meeting.Research result shows a significant correlation on Suhardi learning model to cognitiveability of elementary school children (t = 3,13 dan p = 0,002).Kata Kunci: Pembelajaran Bola Voli, Kognitif.